Attention-dependent coupling with forebrain and brainstem neuromodulatory nuclei differs across the lifespan - Nicholas G. Cicero; Elizabeth Riley; Khena M. Swallow; Eve De Rosa; Adam Anderson (GeroScience, 2025)
Attentional states reflect the changing behavioral relevance of stimuli in one’s environment, having important consequences for learning and memory. Supporting well-established cortical contributions, attentional states are hypothesized to originate from subcortical neuromodulatory nuclei, such as the basal forebrain (BF) and locus coeruleus (LC), which are among the first to change with aging. Here, we characterized the interplay between BF and LC neuromodulatory nuclei and their relation to two common afferent cortical targets important for attention and memory, the posterior cingulate cortex and hippocampus, across the adult lifespan. Using an auditory target discrimination task during functional MRI, we examined the influence of attentional and behavioral salience on task-dependent functional connectivity in younger (19–45 years) and older adults (66–86 years). In younger adults, BF functional connectivity was largely driven by target processing, while LC connectivity was associated with distractor processing. These patterns are reversed in older adults. This age-dependent connectivity pattern generalized to the nucleus basalis of Meynert and medial septal subnuclei. Preliminary data from middle-aged adults indicates a transitional stage in BF and LC functional connectivity. Overall, these results reveal distinct roles of subcortical neuromodulatory systems in attentional salience related to behavioral relevance and their potential reversed roles with aging, consistent with managing increased salience of behaviorally irrelevant distraction in older adults. Such prominent differences in functional coupling across the lifespan from these subcortical neuromodulatory nuclei suggests they may be drivers of widespread cortical changes in neurocognitive aging, and middle age as an opportune time for intervention.

Busting the dust: Evaluating local vs distal sources in Quaternary sediments at Thirlmere Lakes - Matthew S. Forbes; Samuel K. Marx; Tim J. Cohen; Bryce Sherborne-Higgins; Alexander Francke; Germanas Peleckis; Brian G. Jones; Anthony Dosseto; Haidee Cadd; Elizabeth Swallow; Mark Raven; Dioni I. Cendón; et al. (Applied Geochemistry, 2024)

Nonlinear changes in pupillary attentional orienting responses across the lifespan - Elizabeth Riley; Hamid Turker; Dongliang Wang; Khena M Swallow; Adam K Anderson; Eve De Rosa (GeroScience, 2023)
The cognitive aging process is not necessarily linear. Central task-evoked pupillary responses, representing a brainstem-pupil relationship, may vary across the lifespan. Thus we examined, in 75 adults ranging in age from 19 to 86, whether task-evoked pupillary responses to an attention task may serve in as an index of cognitive aging. This is because the locus coeruleus (LC), located in the brainstem, is not only among the earliest sites of degeneration in pathological aging, but also supports both attentional and pupillary behaviors. We assessed brief, task-evoked phasic attentional orienting to behaviorally relevant and irrelevant auditory tones, stimuli known specifically to recruit the LC in the brainstem and evoke pupillary responses. Due to potential nonlinear changes across the lifespan, we used a novel data-driven analysis on 6 dynamic pupillary behaviors on 10% of the data to reveal cut off points that best characterized the three age bands: young (19–41 years old), middle aged (42–68 years old), and older adults (69 + years old). Follow-up analyses on independent data, the remaining 90%, revealed age-related changes such as monotonic decreases in tonic pupillary diameter and dynamic range, along with curvilinear phasic pupillary responses to the behaviorally relevant target events, increasing in the middle-aged group and then decreasing in the older group. Additionally, the older group showed decreased differentiation of pupillary responses between target and distractor events. This pattern is consistent with potential compensatory LC activity in midlife that is diminished in old age, resulting in decreased adaptive gain. Beyond regulating responses to light, pupillary dynamics reveal a nonlinear capacity for neurally mediated gain across the lifespan, thus providing evidence in support of the LC adaptive gain hypothesis.

Use of phospholipid fatty acid analysis as phenotypic biomarkers for soil health and the influence of management practices - Charlotte E. Norris; Mathew J.B. Swallow; Daniel Liptzin; Michael Cope; G. Mac Bean; Shannon B. Cappellazzi; Kelsey L.H. Greub; Elizabeth L. Rieke; Paul W. Tracy; Cristine L.S. Morgan; C. Wayne Honeycutt (Applied Soil Ecology, 2023)